Incidence of recurrent venous thromboembolism of patients after termination of treatment with ximelagatran - Harenberg, Job; Jörg, Ingrid; Weiß, Christel (European journal of clinical pharmacology, 2006)
Recurrent thromboembolic events may occur after termination of anticoagulant therapy for acute venous thromboembolism (VTE) using oral direct thrombin inhibitor ximelagatran.